COMPETENCY OF ISLAMIC RELIGIOUS COUNSELORS IN PREVENTING ONLINE GAMBLING IN TANJUNG TIRAM DISTRICT, BATU BARA REGENCY - Salman; Sazali, Hasan; Efendi, Erwan (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2025)
The increasingly rampant phenomenon of online gambling in the digital space is a serious challenge to fostering community morals, especially among the younger generation. This study aims to examine the competence of Islamic religious instructors in addressing this issue through the use of digital technology, with a focus on Tanjung Tiram District, Batu Bara Regency. Using a qualitative approach with in-depth interview techniques and analyzed using NVivo software, this study explores the ability of instructors to utilize social media, compile educational content, and build effective da'wah communication in the digital space. The results of the study show that instructors such as Edi Yanto and Kamelia Sambas already possess basic digital competencies that support the effectiveness of da'wah, including the use of Facebook to convey religious messages and warnings about the dangers of online gambling. However, technical limitations, such as mastering visual design and video editing, remain significant obstacles. This study concludes that synergy between religious competence and digital skills is essential for counseling to operate effectively in a digital context and reach digitally active levels of society. These findings provide a basis for developing digital training for religious instructors as part of a da'wah-based social prevention strategy.